The influence of personality traits on private retirement savings in Germany - Konrad C. Schäfer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
This paper analyzes private retirement savings, the amount for German individuals and how these savings are influenced by personality traits. With the 2002 to 2009 cross section of the Socio-Economic Panel for Germany (SOEP), it is investigated how the Big-Five and the Locus of Control influence the decision to have private retirement savings, and the estimated amount of these savings. Results indicate a positive effect for Extraversion and a negative effect for Agreeableness on the probability to have such savings. Extraversion also positively effects the size of retirement related savings as does having an more internal Locus of Control. Similar to the probability to have retirement savings Agreeableness also reduces the expected amount of such savings. Personality traits only seem to influence the retirement savings if the individual has scores further away from the average of the specific trait. Additionally regressions are implemented that include the personality measures as dummies to allow for non-linear effects. Furthermore, other types of wealth accumulation such as house related savings are investigated to study how the effects might differ for different types of wealth accumulation.
Keywords: C34; C35; J26; J32; 330; Non-cognitive skills; Big-Five; Locus of Control; retirement